PUTUSAN HAKIM PIDANA YANG MELAMPAUI TUNTUTAN JAKSA PENUNTUT UMUM - Yogi Indra Permana, I Putu; Artha, I Gede; Sudjana, I Ketut (Kertha Negara : Journal Ilmu Hukum, 2013)
In societal life frequently public interest impinged by someone, to evoke feel safe and justice in society, need the existence of process to handle someone bothering the importance. Law arrange the mentioned of is so-called with Procedure of criminal which passing steps that is investigation, prosecution pre, Prosecution, and also Conference. Process Conference represent last process in its solution, where product exit punish in the form of Decision. Sometimes Decision dropped by Judge unlike what asked by Publik Procecutor in its Libel. In dropping proper crime there are some factor constitutoning judge in dropping crime, that is among others Letter Assertion, Threat Crime of Asserted Section, Earn not it Publik Procecutor Prove its Assertion, and Sense Of Justice in society. But besides factor above, Judge is not quit of Principle of justices Event Crime in bringing to justice crime. Thereby Judge drop unattached Decision with Demand Publik Procecutor, because of Decision Judge taken pursuant to Process Verification and also Letter Assertion and Confidence Of Judge.
Keywords: Criminal Judge, Decision Crime, Abysmal, Demand Publik Procecutor